MANAJEMEN MUTU DALAM MENINGKATKAN KOMPETENSI PROFESIONAL PENDDIDIK DI SMA ASSYABROWIYAH DERBING KEC. KETAPANG KAB. SAMPANG - DIN MUHAMMAD ZAKARIYA; Moh. Rubin (Jurnal Penelitian dan Pendidikan, 2023)
To improve professional competence of educators as mandated by laws and government regulations, at Assyabrowiyah Derbing Pancor High School, quality management is necessary to create quality, professional, productive, and highly committed educator resources. It was to overcome the deterioration in the professional competence of educators which has been one of the problems of education, especially in schools.This study aimed to explore and described management practices related to improving the professional competence of educators at SMA Assyabrowiyah Derbing Pancor, to achieve this goal, the researcher used a qualitative approach in a natural setting. The data collection was by unstructured interviews, observation and documentation. The object of the research was educators and education staff as well as students of 9th class and 11th class at Assyabrowiyah Derbing Pancor Senior High School, East Java.This research found that the improvement the professional competence of educators has been going well at Assyabrowiyah Derbing Pancor Senior High School. It could be proven through the guidance of educators such as: education and training, workshops, seminars, MGMP, involving educators in certification programs, their welfare was met, provision of adequate facilities, supervision and assessment, planning and quality control of educators. These forms of training could be a determining factor in increasing the professional competence of educators Kata Kunci : Educator Professional Competency Management